The 10-Item Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) for Functional and Cosmetic Rhinoplasty - Moubayed, Sami P. (JAMA Facial Plast Surg, 2017)
IMPORTANCE: Rhinoplasty is a common operation in which shape and function are intimately related, whether the procedure is cosmetic, functional, or combined in nature. There is currently no properly developed and validated patient-reported outcome measure (PROM) to evaluate both functional and cosmetic components of rhinoplasty. OBJECTIVE: To develop, validate, and field test the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) to evaluate both functional and cosmetic outcomes of rhinoplasty. DESIGN, SETTING, AND PARTICIPANTS: Survey development study between October 2016 and April 2017 in a tertiary referral facial plastic and reconstructive surgery clinic. Preoperative and postoperative adult patients undergoing rhinoplasty, whether cosmetic or reconstructive, were included. A fifth group of adult nonrhinoplasty patients (facial cosmetic or reconstructive) were also included for the field test. MAIN OUTCOMES AND MEASURES: Generated and reduced items, psychometric validation measures of the SCHNOS, and differences on scales between groups. RESULTS: For survey development, a total of 18 patients and 5 experts were interviewed. Of these patients, 5 were male, and 13 were female. Their mean (SD) age was 38 (14.8) years (range, 20-64 years). Field testing included 191 patients (67% were women and the mean [SD] age was 41.5 [15.8] years). A total of 10 items were included after generation, cognitive interviews, and item reduction. The 10 items represent 2 domains: nasal obstruction (first 4 items) and nasal cosmesis (last 6 items). For both domains, Cronbach α was excellent: 0.94 (95% CI, 0.92-0.95) for obstruction and 0.94 (95% CI, 0.93-0.95) for cosmesis. Exploratory factor analysis using scree plots for each domain showed that the domains are unidimensional in nature with each domain evaluating what it is intended to assess (nasal obstruction and cosmesis). The factor loading estimates were high for all the items, varying from 0.74 to 0.92. Kruskal-Wallis testing showed a significance level of P < .001 when evaluating the difference between groups (preoperative cosmetic, postoperative cosmetic, preoperative functional, postoperative functional, and nonrhinoplasty) for all individual questions, composite scores, and Nasal Obstruction Symptom Evaluation (NOSE) score. Correlations between the obstruction composite score and the NOSE scores were r = 0.943 (P < .001), which is very strong. The obstruction and cosmesis composite scores were only weakly correlated (r = 0.388; P < .001). CONCLUSIONS AND RELEVANCE: We have developed and validated a new PROM to evaluate both functional and cosmetic rhinoplasty patients. The domains of obstruction and cosmesis were found to be internally consistent and unidimensional. The SCHNOS provides a short, validated questionnaire that we recommend for use in all functional or cosmetic rhinoplasty patients. LEVEL OF EVIDENCE: N/A.